2022
DOI: 10.1038/s41598-022-15761-y
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity stimulation of aortic baroreceptor afferent fibers as a potential therapeutic alternative for hypertension treatment

Abstract: Carotid baroreceptor stimulation has been clinically explored for antihypertensive benefits, but neuromodulation of aortic baroreceptor afferents remains unexplored for potential translation into the clinic. Published studies have used supramaximal stimulations, which are unphysiological and energy inefficient. The objective of the present study was to identify optimal low-charge nerve stimulation parameters that would provide a clinically-relevant (20–30 mmHg) decrease in mean arterial pressure (MAP) in anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…All raw data traces were smoothed over a 1 s time constant and subsequently converted into 5 s bins. Measures of vascular resistance were calculated by dividing MAP by the blood flow values recorded from the mesenteric and femoral vascular beds, as described previously [21,22,25,28]. Resting baseline levels were recorded over a 40 s period prior to starting the neurostimulation protocol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All raw data traces were smoothed over a 1 s time constant and subsequently converted into 5 s bins. Measures of vascular resistance were calculated by dividing MAP by the blood flow values recorded from the mesenteric and femoral vascular beds, as described previously [21,22,25,28]. Resting baseline levels were recorded over a 40 s period prior to starting the neurostimulation protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Depth of anesthesia was confirmed throughout the experiment by absence of reflex response to tactile (corneal stroking) and noxious (hindpaw pinch) stimuli. The rationale for choice of anesthesia has been described in a previous study from our laboratory [25]. Core body temperature was maintained between 36.5 and 37 °C using a heating blanket (T/Pump warm water re-circulator, Stryker Medical, Michigan, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, direct electrical stimulation of the baroreceptor afferents in spontaneously hypertensive rats (SHR) carries a massive potential to functionally assess the baroreflex circuit in relation to hypertension, identify novel targets for BP modulation and discover new methods for enhancing and improving current BAT technology. Indeed, using the SHR model, we have recently identified the ‘aortic’ baroreceptor afferents as a viable alternative neuromodulation target to ‘carotid’ baroreceptor stimulation in lowering mean arterial pressure (MAP) [ 12 ]. We have further showed that ‘low intensity’ stimulation is an effective alternate way for neuromodulation of the aortic baroreceptor afferents, enabling low-energy consumption to induce a clinically relevant reduction in MAP levels in the SHRs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%